Method of Doppler Frequency Spread Estimation for High-Mobility OFDM Systems - Feng Zhao; Xihong Sun (International Journal of Distributed Sensor Networks)
A method of Doppler frequency spread (DFS) estimation algorithm is discussed which is suitable for high-mobility Orthogonal Frequency Division Multiplexing (OFDM) systems. DFS is a main factor which may mitigate the performance of system. The proposed method is based on autocorrelation function algorithm of received signal which utilizes cyclic prefix (CP) to estimate Doppler spread. The estimation algorithm uses least square (LS) method between the autocorrelation function of received signal and the zero-order Bessel function which is approximated by the expansion of power series. Then the estimation bias is analyzed and using polynomial fitting method can effectively correct estimation error at different DFS, respectively. Compared with the previously proposed method, the estimation performance of DFS in the proposed method has better performance. Simulation results show that when sufficient elements are used, the proposed scheme can effectively estimate DFS and can be applied into high-mobility OFDM systems.